Aplicación de biopelículas desarrolladas a partir de productos infrautilizados de Zea mays l. y Musa acuminata en productos de IV y V gama - Rosero Guerra, María Victoria (2021)
The purpose of this research work is to apply a new option for biodegradable wrapping in order to replace plastics of petrochemical origin with degradable biofilms made with banana starch and black corn. The techniques used in this research are: casting for V range products and the immersion method for IV range products. The work was carried out in the laboratories of the Career of Agro-industrial Engineering and in the INVAGRO research group from the Universidad Nacional de Chimborazo. 3 treatments were designed for the production of biofilms: T1 (50% banana starch, 50% black corn starch) and T2 (biofilms with 75% banana starch, 25% black corn starch), and white corresponding to the sample with synthetic plastic coating, applied in products of IV range (grapes and strawberries) and V range (fresh cheese and ground beef). In the IV and V range products, the physicochemical properties were evaluated: pH, titratable acidity, refractometry and humidity, additionally the fat analysis was carried out for the fresh cheese. The microbiological requirements were determined by the NTE INEN standards and the DIGESA MINSA standard, a sanitary standard that establishes the microbiological criteria of sanitary quality and safety for food and beverages for human consumption. The results obtained were analyzed by means of an analysis of variance (ANOVA), showing statistical differences (p <0.05) in the moisture content, pH, titratable acidity, fat and refractometric index, as for the microbiological analysis the growth of microorganisms in the food tested. It is concluded that the biofilms that offered the best results are: T2 in strawberries, grapes and fresh cheese, T1 for ground beef, this becomes an environmentally friendly coating alternative that ensures the microbiological quality of the products and therefore the health of consumers.